2010
DOI: 10.5251/abjna.2010.1.5.886.893
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of selected Kenyan potato cultivars for processing into potato crisps

Abstract: There has been tremendous increase in the demand and consumption of potato crisps as snack in Kenya. This has however, not been paralleled by development of appropriate raw materials. Many potato varieties and clones have been developed through breeding, but these have not been adequately evaluated for crisps processing. This study was therefore designed to evaluate the newly developed potato cultivars for processing into quality crisps. Twenty four potato cultivars including eighteen varieties and six clones … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 8 publications
1
32
0
Order By: Relevance
“…Zafira produced the lowest (1.05) mean value. In a similar study Abong et al (2010) found that specific gravity and dry matter contents had significant difference among potato varieties. The interaction of K and varieties had no significant influence on specific gravity.…”
Section: Specific Gravitymentioning
confidence: 80%
See 1 more Smart Citation
“…Zafira produced the lowest (1.05) mean value. In a similar study Abong et al (2010) found that specific gravity and dry matter contents had significant difference among potato varieties. The interaction of K and varieties had no significant influence on specific gravity.…”
Section: Specific Gravitymentioning
confidence: 80%
“…Table 2 indicates that Ajiba which had highest tuber number produced smallest tuber size (4.84 cm). Similarly, Abong, Okoth, Imungi and Kabira (2010) found that tuber diameter varied significantly among potato cultivars. This could be due to the peculiar genetic characteristics of the varieties: Ajiba, Zafira and Picasso produce large, large oval to long-oval, and very large to large with red eyes tubers, respectively (NIVAP, 2011).…”
Section: Tuber Diametermentioning
confidence: 99%
“…Table 3 indicates that Ajiba which had highest tuber number produced smallest tuber size (4.84 cm). Similarly, [37] found that tuber diameter varied significantly among potato cultivars. This could be due to the peculiar genetic characteristics of the varieties: Ajiba, Zafira and Picasso produce large, large oval to long-oval, and very large to large with red eyes tubers, respectively [38].…”
Section: Tuber Diametermentioning
confidence: 99%
“…Potato consumption as processed and fresh food is also increasing considerably in Bangladesh (Brown, 2005). Abong et al (2009) studied the storage and processing characteristics of red skinned, Kerr's pink, white skinned and Desiree potato varieties. Although, potato product manufacturers are using High Yielding Variety (HYV) consumers in some parts of northern region of Bangladesh also prefer the local potato cultivars, because of taste, flavor, color, ambient storage ability local cultivars of potato (Fig.…”
Section: Introductionmentioning
confidence: 99%